Gestão e sucessão de empresas familiares: uma revisão de literatura. - Moraes Filho, Antônio Trindade de (2009)
The present work comprises proposals for some gaps found in the research made about family businesses, by means of analysis of the scientific production, with conceptual focus as well in the intergerational relationship, of all papers published in the events of the National Association of Post-graduation and Research on Administration (EnANPAD, Eneo, 3ES e EnGPR), and in the journals RAC, RAE, RAUSP and O&S, within the period from 1961 to 2008, besides consultations in the libraries of the Getúlio Vargas Foundation, in Rio de Janeiro (in December 2008) and in São Paulo (in December 2008 and May 2009). Nine criteria of analysis were used: research in family businesses, frequency of the publications, quotations and references, most prolific authors, institutions that most publish, average of papers published, theoretical bases of the investigation, conceptual aspects and father and son. From the 154 papers found, which a priori were directed to this theme, only 89 were included for presenting adherence to the aims of the research. The results reveal various contradictions among the studies, both from the conceptual point of view and the methodogical one; it is not possible, yet, to find a concept of family business; diverse factors have influence in the negative image associated to those organizations, but which are not able to dim the light of those which are the principal responsible for wealth distribution, job generation and economical growth, in Brazil and in the world; and when they take advantage of their competitive status, they are able of standing out from the competitors and revert any situation which are against their interest.